Oracle SOA Suite 11g handbook [ - Jellema, Lucas (McGraw Hill, 2010)
"Design and implement an agile service-oriented enterprisecomputing infrastructure using the detailed information inthis Oracle Press guide. Written by an Oracle ACE director,Oracle SOA Suite 11g Handbook uses a hands-on case study to illustrate each programming, management, and governanceconcept. Get expert techniques for modeling complex business processes and deploying and securing Web services,while maximizing decoupling and code reuse. - Install Oracle SOA Suite 11g or migrate from a previous version - Develop reusable application components using SCA and SDO - Model processes using BPEL, BPMN, and human task components - Establish dynamic routing and logging rules with Oracle Mediator - Apply the principles of Oracle Event-Driven Architecture Suite through Oracle Complex Event Processing, the Event Delivery Network, and the BAM Server - Benefit from the power of Java through the Spring component and the interaction with Oracle Application Development Framework - Transpose and validate heterogeneous data using the Oracle Service Bus - Design, test, and deploy composite applications from the Oracle Fusion Middleware Control Console "-- Provided by publisher